Numerical Modeling of Brittle Fracture Using the Phase-Field Method - Saeed, Ghaid (2025)
A Master of Science thesis in Mathematics by Ghaid Saeed entitled, “Numerical Modeling of Brittle Fracture Using the Phase-Field Method”, submitted in July 2025. Thesis advisor is Dr. Youssef Belhamadia. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).